Peran Aparat Penegak Hukum Dalam Menangani Tindak Pidana Penipuan Arisan Online Diwilayah Hukum Kepoliosian Daerah Gorontalo - Tanaiyo, Abdul Wahidin DP; Nurmaia, Leni Dwi; Kasim, Ramdhan (CV. ITTC INDONESIA, 2023)
This study aims to find out how the regulation of criminal acts of online arisan fraud is based on Indonesian law, what is the role of law enforcement officials in dealing with criminal acts of online arisan fraud in the jurisdiction of the Gorontalo regional police, and how is the process for solving criminal acts of online arisan fraud in the jurisdiction of the Gorontalo regional police. .. This study uses empirical legal research methods which are conducted by collecting data through observation and interviews. The results of the study indicate that there are criminal cases of fraud under the guise of online arisan in the jurisdiction of the Gorontalo regional police, the need for strict law enforcement by the police in carrying out their duties, especially in the management of investigations carried out by the police so that they can catch any perpetrators of fraud under the guise of online arisan such as which has been confirmed by the applicable law. The Gorontalo Regional Police (Polda) is the executor of police duties in Gorontalo Province. The Gorontalo Regional Police is led by a two-star regional police chief. The formation of the Gorontalo Regional Police occurred after the regional division of North Sulawesi Province. There is a reform policy within the Polda Institution, including the establishment of a new Polda within the ranks of the National Police. In addition, there are a number of cases of criminal acts of online arisan fraud that occurred in the jurisdiction of the Gorontalo Regional Police. As a prevention effort, the Gorontalo Regional Police conducted outreach to the public about online arisan and the risks of fraud that might occur. Polda Gorontalo organizes meetings, seminars and outreach campaigns to raise public awareness about how to avoid fraud in online gatherings. The Gorontalo Regional Police provided information on steps to be taken, such as verifying the organizers of the social gathering, checking reputation, and not sharing personal information carelessly. In addition, as an investigator for the Gorontalo Regional Police, he also plays a role in eradicating criminal acts of online gathering fraud and receiving reports from victims of fraud and conducting in-depth investigations of the case. In the legal settlement of the perpetrators of the crime of online arisan fraud, the Gorontalo Police took non-formal and formal routes and a restorative justice approach could be an option to restore material losses experienced by victims. However, the process of handling cases of online arisan fraud is often complex and takes quite a long time.